Peak running speeds in professional male football: influence of division and playing position - Fahey, J. T.; Aldred, K.; Greig, M.; Rhodes, D. (The Journal of Strength and Conditioning Research, 2023)
Well-established physical demands of competitive professional football facilitate prescription and monitoring of training. However, many factors influence these physical demands with implications for efficacious practice. Match-play data were analyzed over 2 seasons using global positioning systems technology, differentiating English Championship (33 matches) and League One (27 matches) demands. Playing position categorized wide and central defenders and midfielders and forwards. Peak running speeds defined the outcome measure, assessing the influence of the competition level and playing position across 1, 5, and 10-minute rolling average durations using a linear mixed model. Significant effects were detected for the competition level (F1,324.5 = 5.44, p = 0.02) and playing position (F4,328.3 = 89.90, p < 0.001). League One matches demonstrated greater peak running speeds than Championship matches (mean difference = 2.72 m·min-1 [95% confidence intervals: 0.4, 5.0]). No difference was observed between central and wide midfielders (mean difference = 0.62 m·min-1 [95% confidence intervals: -3.1, 4.3]). Wide midfielders presented faster peak running speeds than forwards (mean difference = 18 m·min-1 [95% confidence intervals:14.1, 22.1], p < 0.05), central defenders (mean difference = 25 m·min-1 [95% confidence intervals: 21.7, 29.8], p < 0.05), and wide defenders (mean difference = 12 m·min-1 [95% confidence intervals: 8.2, 16.5], p < 0.05). Interaction effects were found for division*position (F4,328.3 = 2.57, p = 0.038) demonstrating greater running speeds in League One, except for central defenders. Wide midfielders presented greater peak 1-minute running speeds, whereas 5 and 10-minute peak running speeds were greatest in central midfielders. The sensitivity of peak running speeds to competition level and playing position has implications for training prescription, monitoring particularly when transitioning between competition levels, determining and monitoring positional training intensities, and objective targets for progressive overload during rehabilitation.